Reverse engineering of conjugated microporous polymers: defect structures of tetrakis(4-ethynylphenyl)stannane networks - Uptmoor, Andrea Christina; Freudenberg, Jan; Schwaebel, S. Thimon; Paulus, Fabian; Rominger, Frank; Hinkel, Felix Peter; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2015)
Two different conjugated microporous polymers (CMPs) based on tetrakis(4-ethynylphenyl)stannane as the repeating unit were synthesized and their BET surfaces and thermal properties were investigated. The first direct method to elucidate the molecular structure of the organic linkers between the tin centers by digestion of the CMP is described. Selective cleavage of the tin-carbon bonds with chloroacetic acid afforded the isolated bridging units and provided insight into the surprisingly varied chemical composition of these networks.
Gesehen am 07.07.2020